An integrated approach to surveying the archaeological landscapes of Yemen - Banks, R; Fradley, M; Schiettecatte, J; Zerbini, A (Archaeopress, 2017)
This paper presents recent research by the Endangered Archaeology in the Middle East and North Africa (EAMENA) project at the Universities of Oxford and Leicester, and Jérémie Schiettecatte at Centre National de la Recherche Scientifique (CNRS) in Paris. It critically investigates the contribution of documenting sites through recent remote surveys using freely available satellite imagery to improve our understanding of ancient landscapes in Yemen, and the role of field surveys and excavations in this process. The documentation and recording includes an assessment of the threat to sites with a view to improving their protection in the future.